Water Management Problems in Bihar and Suggestions for Improvement - jha, H.N. (Journal of Soil and Water Conservation, 2022)
Bihar is predominatly an agricultural state with limited land resources and relentless rise in population. On the map of India, it occupies 10th position in geographical area second position in population after U.P. and ranks third in density of population (691/square mile) after Kerala (1125/Sq. mile) and West Bengal (1031/Sq. mile). 86% of the population depends on agriculture as against the All India average of 70 per cent. Achieving self sufficiency in food is, therefore, an acute problem for the state. Irrigation, which is the prerequisite for increased food production, needs special attention as to only above 20-25 per cent of the total cultivated land, irrigation facilities have been extended so far. In order that irrigation may be a better effective tool in stepping up food production, a special care is to be taken for the problems related to watar management which ultimately stand in the way of efficient farming. The different water management problems which the state is facing presently and suggestions for their improvement have been discussed in the subsequent pages.